Celiac Disease Assocaited with Primary Biliary Cirrhosis in a Coast Salish Native - Hugh J Freeman (Canadian Journal of Gastroenterology)
A 41-year-old Coast Salish female was initially diagnosed with typical features of classical adult celiac disease. Clinical and pathological features of primary biliary cirrhosis were also present, along with a familial history of insulin-dependent diabetes. Later, childhood celiac disease was detected in a male first-degree relative with diabetes. These patients are the first reported natives in Canada with celiac disease, a disorder believed to be genetically based but dependent on environmental factors for its clinical expression. The recognition of a ‘new’ disease in the setting of an aboriginal population may reflect geographical and climatic factors that permitted subsistence of this culturally complex food-gathering society up until most recent historical times, followed by adaptation of this society to European-based agricultural methods, particularly wheat cultivation.